A review on recent progress in lead-free perovskite-based solar cell materials - Shrestha, Chhabi Kumar; Bhandari, Prakash (Himalayan Physics, 2025)
Although lead-based perovskite solar cells (PSCs) exhibit high power conversion efficiency (PCE), their global commercialization remains limited. It faces challenges due to the toxicity of lead, which raises environmental concerns. Consequently, researchers are focused on identifying such alternative elements that can replace lead without significantly changing its efficiency, stability, and cost-effectiveness. Therefore, this review focuses on potential candidates such as tin (Sn), bismuth (Bi), antimony (Sb), titanium (Ti), and copper (Cu), along with their properties, challenges, and possibilities. Furthermore, the double perovskites, which have emerged as a substitute route for obtaining stable, effective, and non-toxic PSCs, are also reviewed. Additionally, this review paper summarizes the methods for enhancing stability and efficiency by adding certain additives to create non-toxic and lead-free perovskites. Moreover, recent developments and advanced technologies employed in the development of lead-free PSCs are also discussed, along with their future direction.